2022
DOI: 10.23887/jish.v11i1.41106
|View full text |Cite
|
Sign up to set email alerts
|

Community Livelihood Diversification as a Result of Mining Industry Activities: A Case Study of Soligi Village, South Halmahera

Abstract: Indonesia is one of the world's largest archipelagic countries. Diversification is the process of increasing household economic income in various sectors to improve welfare and survival opportunities. This study demonstrates that the people of Obi Island's livelihoods are diversifying due to mining and pressure from the immigrant population. This study is necessary to determine how mining depletes natural resources affects the livelihood strategies of the Indonesian archipelagic community, particularly in Malu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…Hasil temuan ini sesuai dengan penelitian Izzudin et al, (2022) yang menjelaskan bahwa masyarakat pesisir akan melakukan difersifikasi pekerjaan apabila ada situasi yang mengancan penghidupan mereka karena ketergantungan pada sumberdaya alam. Selain itu, studi Andiny (2020) di Desa Kuala Langsa, Aceh, menyatakan bahwa pengembangan ekowisata hutan mangrove dapat meningkatkan aktivitas masyarakat.…”
Section: Simpulan Dan Saranunclassified
“…Hasil temuan ini sesuai dengan penelitian Izzudin et al, (2022) yang menjelaskan bahwa masyarakat pesisir akan melakukan difersifikasi pekerjaan apabila ada situasi yang mengancan penghidupan mereka karena ketergantungan pada sumberdaya alam. Selain itu, studi Andiny (2020) di Desa Kuala Langsa, Aceh, menyatakan bahwa pengembangan ekowisata hutan mangrove dapat meningkatkan aktivitas masyarakat.…”
Section: Simpulan Dan Saranunclassified
“…Other studies also show that coal mining activities in Separi Village have various impacts on the social structure of the community and the presence of coal mining is not only seen in changes in livelihoods but also in social and economic aspects which include community income levels and non-agricultural employment opportunities (Nurislam et al, 2022). Economically, the presence of the mining industry contributes to the diversification of people's livelihoods, such as opening up new jobs for local people as company employees (Izzudin et al, 2022). Another study conducted by Ometehinse and Bankole (2019) found that the implications of mining exploration and exploitation have resulted in the loss of homes for residents, loss of biodiversity and the use of chemicals has the potential to disrupt the health of workers and communities around mining areas.…”
Section: Introductionmentioning
confidence: 99%